PENGARUH PENERBITAN SURAT PAKSA DAN SURAT PERINTAH PENYITAAN TERHADAP PENERIMAAN PPH PASAL 25 WAJIB PAJAK ORANG PRIBADI - Arslinda Dwi Pratiwi; Setu Setyawan (Jurnal Akademi Akuntansi, 2018)
Tax receipts are one source of income that has a major impact on the prosperity and welfare of the community.  In 2016, 81.75% of the country's revenues come from taxes. There is a decrease in the amount of income tax article 25 WP-OP, in 2016 amounted to 36.12% led to reduced tax revenue. One of the things that most influence the income tax is the tax audit that generates tax assessment letters and tax collection. This study purpose to examine the effect of Issuance of forced letter and confiscation warrant on Income Tax Article 25 WP-OP. in this research is KPP Pratama Gresik Utara in 2015-2017. In this study, the sample amounted to 35 by using multiple linear regression analysis techniques. The results showed that simultaneous issuance of forced letter and confiscation warrant have a significant effect on Income Tax Article 25 WP-OP